2021
DOI: 10.1021/acs.macromol.1c00575
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Control of the Three-Dimensional Confined Assembly of Charged Block Copolymers in Emulsion Droplets

Abstract: Understanding the microphase separation of charged block copolymers (BCPs) is very important for the development of functional materials with tunable structures. Although the morphological behavior of charged BCPs in bulk and in solution has been explored, the three-dimensional (3D) confined self-assembly of charged BCPs is still unknown. Here, we report the confined assembly of positively charged polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) in emulsion droplets. The fraction of charged segments can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…In contrast, the cylindrical structures differ mainly in orientation and shape, including biconcave disk (Dk), truncated single helix (H 1 ), two crossed cylinders (C 2 × ), single toroid (T 1 ), single toroid plus one sphere (T 1 S), single toroid plus a pair of spheres at the two sides (ST 1 S), double toroids (T 2 ), twisted double toroids (tT 2 ), three-hole cage (CG 3 ), four-hole cage (CG 4 ), and six-hole cage (CG 6 ). It is necessary to mention that some similar structures were observed in the literature though their stability is rarely discussed. ,,,,, For example, Chen et al. observed a series of spherical structures such as S 1 , S 2 , S 4 , and S 6 …”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, the cylindrical structures differ mainly in orientation and shape, including biconcave disk (Dk), truncated single helix (H 1 ), two crossed cylinders (C 2 × ), single toroid (T 1 ), single toroid plus one sphere (T 1 S), single toroid plus a pair of spheres at the two sides (ST 1 S), double toroids (T 2 ), twisted double toroids (tT 2 ), three-hole cage (CG 3 ), four-hole cage (CG 4 ), and six-hole cage (CG 6 ). It is necessary to mention that some similar structures were observed in the literature though their stability is rarely discussed. ,,,,, For example, Chen et al. observed a series of spherical structures such as S 1 , S 2 , S 4 , and S 6 …”
Section: Resultsmentioning
confidence: 86%
“…The self-assembly of block copolymers under 3D spherical confinement has also attracted a certain amount of research interest. Especially, the spherically 3D-confined block copolymer systems can be realized by preparing block copolymer nanoparticles using a self-organized precipitation method in experiments. It is worth noting that these structured nanoparticles exhibit promising application potential in photonic materials. , Higuchi et al studied the self-assembly of lamellar diblock copolymers confined in the nanoparticles with a nearly neural surface . They found that if the size of the nanoparticle is large enough, stacked lamellar structure can be formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In this system, the emulsion droplets act as a soft and mobile template for the BCP self-assembly, which dominates the morphologies and shapes of the BCP particles. Therefore, various BCP particles with different shapes, such as onion-like particles, [12][13][14] ellipsoidal particles, [15][16][17] Janus particles, 18,19 and sieve-like particles, 20,21 have been produced. In general, these particles are relatively stable since this system normally reaches a metastable state or a steady state, that is, it is a great challenge to realize morphology transformation of the as-prepared BCP particles due to the existence of energy barriers.…”
mentioning
confidence: 99%
“…In particular, the introduction of stimuli-responsive additives not only modulates the interactions between the BCP blocks and the additives, but also provides the possibility of the shape transformation of BCP particles triggered by external stimuli. 13,23,25,27 In a pioneering work, Kim and co-workers incorporated temperature-responsive poly(N-isopropylacrylamide) (PNIPAM) into polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) in emulsion confined self-assembly; a reversible shape transformation between convex lens-shaped particles and ellipsoid-shaped particles was successfully demonstrated, which was attributed to the temperature response of PNIPAM. 25 However, these strategies are interventional methods that are used to change the physical or chemical properties of the system.…”
mentioning
confidence: 99%